2010
DOI: 10.1016/j.semcdb.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma-associated fibroblasts are a rate-limiting determinant for tumour progression

Abstract: Tumours are highly complex tissues composed of carcinoma cells and surrounding stroma, which is constructed by various different types of mesenchymal cells and an extracellular matrix (ECM). Carcinoma-associated fibroblasts (CAFs), which consist of both fibroblasts and myofibroblasts, are frequently observed in the stroma of human carcinomas, and their presence in large numbers is often associated with the development of high-grade malignancies and poor prognoses. Moreover, in human tumour xenograft models, CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
251
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(260 citation statements)
references
References 74 publications
3
251
0
6
Order By: Relevance
“…In particular, the tumor-promoting ability of a-SMA-positive CAFs, the myofibroblasts, has been shown in breast, prostate, pancreatic, and skin cancer mouse models (9)(10)(11)(12)(13)(14). Following the observation that 4T1 tumors expressing very high levels of LOXL2 exhibited extensive a-SMA expression compared with 4T1 shLOXL2 tumors, we sought to determine whether LOXL2 could facilitate fibroblast activation and hence play a role in formation of the myofibroblast population of CAFs present in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the tumor-promoting ability of a-SMA-positive CAFs, the myofibroblasts, has been shown in breast, prostate, pancreatic, and skin cancer mouse models (9)(10)(11)(12)(13)(14). Following the observation that 4T1 tumors expressing very high levels of LOXL2 exhibited extensive a-SMA expression compared with 4T1 shLOXL2 tumors, we sought to determine whether LOXL2 could facilitate fibroblast activation and hence play a role in formation of the myofibroblast population of CAFs present in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the growth of breast, prostate, pancreas, and skin cancer cells in mice is significantly enhanced when they are coimplanted with a-SMA-positive CAFs isolated from solid tumors (9)(10)(11)(12)(13)(14). Even nontumorigenic prostate epithelial cells could be induced to form tumors in immunocompromised mice when mixed with CAFs (15).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have highlighted the importance of CAFs in initiation and progression of cancer mediated by the ability of the CAFs to alter important functions in neoplastic cells, such as cell cycle regulation, migration, and death (Shimoda et al, 2010). Interestingly, neoplastic cells of different origins differ in their responses upon stimulation from CAFs (Kadaba et al, 2013), illustrating a unique relationship with CAFs across tumor types.…”
Section: Cafs Trigger Tumor Initiation and Progressionmentioning
confidence: 99%
“…CAFs play an important role in promoting tumor initiation and progression by stimulating angiogenesis and tumor cell growth and invasion (Shimoda et al, 2010). The existence of a large number of CAFs in tumors is often associated with poor prognosis (Maeshima et al, 2002;Surowiak et al, 2006).…”
Section: Fibroblastsmentioning
confidence: 99%